A program for embedding career activities in multiple core business courses. Issue 3 (November 2020) - Crowne, Kerri Anne; Brown, Maureen; Durant, Danielle; Baburaj, Yamuna; Hornberger, Peter; McCloskey, Donna; Vike, Louisa
Abstract: One of the goals of undergraduate business programs is to prepare students for navigating the job market, yet many programs do not effectively incorporate career activities into the curriculum. Often career-focused training is outsourced to a career center or a career services unit of the university or school, which results in a lack of linkage between the student's professional preparedness and their course of study. Additionally, this outsourcing may not ensure full participation of the business students. We present a program for integrating career preparedness activities into the business curriculum across multiple years in conjunction with our university career services, which has been well-received by the student body. The program has two main components: (1) progressive, stepwise career activities are embedded into a core course from each year of the traditional 4-year undergraduate business program, and (2) the activities are graded requirements, making up a portion of how the student is evaluated in that course. This program ensures every student in the school of business is provided with adequate career preparedness training, and the school of business is well-positioned to achieve high job placement rates. Highlights: A multi-course, embedded career program for undergraduate business students. Activities include resumes, interviews, networking, and professional development. Administered by faculty with the assistance of the career office. Embedded in required, core business courses. Appendices provide all necessary materials to administer the program.